Serviço de Referência em Bibliotecas Universitárias: proposta de política aplicada as universidades federais do Nordeste brasileiro - Santos, Izabel Lima dos (2020)
It deals with the Reference Service (RS) in the context of the Libraries of Federal Universities in the Northeast region of Brazil. It presents the following question as a problematic element: how is it possible to structure a policy for the development of the reference service in the libraries of Federal Universities in Northeast Brazil, through an approach on the achievements of this service? Its general objective is to identify reference service practices in the libraries of federal universities in Northeast Brazil and to propose strategies for their dynamization. The general objective is subdivided into three specific objectives: To identify the existing guidelines related to the RS performance in the libraries of federal universities in the Northeast; Establish performance parameters for RS in university libraries and Propose a development policy for RS in libraries of federal universities in the Northeast. Based on these objectives, it presents and discusses the trajectory of policies aimed at universities, especially those dedicated to university libraries. It exposes the historical evolution and discusses the concepts associated with RS, presents its structure and interrelations in the university environment, as well as provides examples of guidelines and actions related to this sector developed by institutions from various parts of the world. Methodologically, it makes use of document analysis, with the analyzed documents being collected on the websites of the 18 institutions investigated, and a semi-structured electronic questionnaire applied to librarians who work in the libraries of the researched federal universities. The collected data were examined based on discourse analysis. From the examination of the data, it concludes that the library systems analyzed, in their majority, carry out reference activities. However, there is a predominance of traditional RS practices. In addition, it was found that there are no guidelines for the performance of the reference service in the researched libraries, but there is, on the part of the librarians, the desire for such resources to be made available. Finally, a policy was proposed to guide the performance and development of RS within the university library.